Grand mal seizure induced by oral theophylline. Issue 4 (August 1976) - Matthay, R A; Matthay, M A; Weinberger, M M
Abstract : A grand mal convulsion occurred in a patient with decompensated cor pulmonale. Although only modest doses of oral theophylline were being administered at the time of the convulsion the serum theophylline level was markedly raised and the theophylline clearance was very low. After treatment for cor pulmonale theophylline clearance improved; however, with the subsequent onset of fever and pneumonia the clearance decreased again, illustrating the potential lability of theophylline clearance.